GEOINFORMATIONAL COMPETENCE OF SENIOR PUPILSAS A COMPONENT OF INFORMATIONCOMPETENCE - Babijchuk, Svitlana M. (Educological discourse, 2015)
Modern education based on the practical use of knowledge, a component of which is the formation among school students specific competence. The study of geoinformation systems in high school based on the formation of geoinformation competence. Geoinformation competence is a component of information competence. The definition of this concept is multifaceted as contains set of competencies that a student should formed.The article considers the practical development geoinformation competence of students' "GIS inGeography" of Kyiv Small Academy of Sciences.